The reasons for the collective withdrawal of African States from the Statute of the International Criminal Court (and their impact on the universal character of the Court) - Abdul Majid, Abker Ali Ahmed (Journal of Economic, Administrative and Legal Sciences, 2017)
The collective withdrawal of the African States from the statute of the International Criminal Court and its repercussions on the universal character of the court is the topic that the study tackled.  The importance of the research is based on the above mentioned collective withdrawal, for it has really weakened the court, simultaneously revealed the deep effect of the African States on the International Criminal Court. In fact this collective work represents a bravery that is rarely seen in our contemporary world. A world that is loaded with unbearable human rights violations, never forgetting that the African States represent the bulk of the court members.  By this, the court is no longer a court, and has been paralyzed once for all. The study aimed at unveiling the justifications, repercussions of the court inception and the extent to which it can intervene in the African home conflicts. A number of research methods were adopted, including: analytical descriptive, the inductive and the historical one. The study produced many results, from which: The majority of the ICC members are Africans, that means the collective withdrawal of the continent members from the court, results in losing the universality of the court, in addition to accusing the African leaders and criminalizing them, led to the mutiny of the leaders, represented in the threat of  the union to choose the collective withdrawal from the statute of the ICC. The end-product of the study told a number of recommendations: The ICC should review the way of running its affairs, negotiate with African countries to withdraw their withdrawal from the ICC in order to maintain its global status. African countries should reconsider the collective withdrawal decision and activate national courts to carry out their duties perfectly.
Keywords: repercussions; collective withdrawal; African countries; the Court; the International Criminal Court